Diversity-Enhancing Selection Acts on a Female Reproductive Protease Family in Four Subspecies of Drosophila mojavensis - Kelleher, Erin S. (Genetics Society of America, 2011)
Protein components of the Drosophila male ejaculate are critical modulators of reproductive success, several of which are known to evolve rapidly. Recent evidence of adaptive evolution in female reproductive tract proteins suggests this pattern may reflect sexual selection at the molecular level. Here we explore the evolutionary dynamics of a five-paralog gene family of female reproductive proteases within geographically isolated subspecies of Drosophila mojavensis. Remarkably, four of five paralogs show exceptionally low differentiation between subspecies and unusually structured haplotypes that suggest the retention of old polymorphisms. These gene genealogies are accompanied by deviations from neutrality consistent with diversifying selection. While diversifying selection has been observed among the reproductive molecules of mammals and marine invertebrates, our study provides the first evidence of this selective regime in any Drosophila reproductive protein, male or female.